WO3/BiVO4 photoanode coated with mesoporous Al2O3 layer for oxidative production of hydrogen peroxide from water with high selectivity. Issue 75 (11th October 2017) - Fuku, Kojiro; Miyase, Yuta; Miseki, Yugo; Gunji, Takahiro; Sayama, Kazuhiro
Abstract : A mesoporous and amorphous Al2 O3 layer coated on WO3 /BiVO4 photoanode significantly facilitated inhibiting the oxidative degradation of generated H2 O2 into O2 on the photoanode, resulting in the achieving excellent H2 O2 selectivity. Abstract : A WO3 /BiVO4 photoanode coated with various metal oxides demonstrated high selectivity (faradaic efficiency) for hydrogen peroxide (H2 O2 ) generation from water (H2 O) under irradiation of simulated solar light in a highly concentrated hydrogen carbonate (KHCO3 ) aqueous solution. A mesoporous and amorphous aluminium oxide (Al2 O3 ) layer significantly facilitated inhibition of the oxidative degradation of generated H2 O2 into oxygen (O2 ) on the photoanode, resulting in unprecedented H2 O2 selectivity ( ca. 80%) and the accumulation (>2500 μM at 50C).